Digital Data Collection "ODK et Digitalisation” - Ouerghemmi, Hassen; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
This presentation was used as training material on October 31, 2023. The training took place at the Office National de l'Olive in Tunis. Participants were all local agents of the ONH, responsible for olive oil and oil market monitoring activities. The presentation began with an introduction to ODK, the rationale behind its use, and the steps involved from downloading the application to sending surveys to a common data sheet.